Pérégrinations du matn d’Ibn ‘Āshir (xviie siècle) : renouveau et réappropriations concurrentielles du malikisme au sein de l’enseignement islamique francophone - Younes Johan Van Praet (Revue des Mondes Musulmans et de la Méditerranée)
Ibn ‘Āshir’s matn (1582–1631) is probably the Maliki law text that most symbolizes Moroccan Malikism. Composed by an illustrious scholar from Fez in the Gregorian 17th century it has been committed to memory very early in the teaching of acts of worship intended for children within the madāris and is at the heart of the program of the Mohammed VI Institute in Rabat which is responsible for the training of the French-Moroccan imams. At the same time, Ibn ‘Āshir’s matn appears as a recent production within the French-speaking edition of the Islamic book like a breath of fresh air. This came as I myself encountered the work of Ibn ‘Āshir during an ethnographic field trip in France, on the transmission of Islamic knowledge. This article proposes a description of the resurgence of matn in a French-speaking context, through teaching practices that take into account the accompanying tensions. The article concludes with a demonstration of how the transmission practices surrounding this matn appear central to understanding some of the contemporary issues that are transforming the French-speaking Islamic scene.